Stability limits of the liquid phase in the layered Mo/Pb/Mo, Mo/Bi/Mo and Mo/In/Mo film systems - Petrushenko, S.I.; Dukarov, S.V.; Sukhov, V.N. (My University, 2016)
The results of the study of supercooling of the fusible metals films between the continuous layers of molybdenum during the crystallization are given. Due to an original in situ technique based on the changes of resistance of samples during heating and cooling directly in the vacuum chamber the values of supercooling in Mo/Pb/Mo, Mo/Bi/Mo, Mo/In/Mo films are determined and the influence of the morphological structure of the bismuth inclusions on the temperature and nature of its supercooled melt crystallization has been found. The substrate temperature change during the condensation of samples, accompanied by a corresponding change in their microstructure, allows realizing both avalanche and diffuse crystallization and changing of supercooling value in the range of 60 to 180 K in Mo/Bi/Mo films.
Keywords: Supercooling; Multilayer films; Electrical resistance; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces